DEVELOPING A HANDOUT BASED ON BANTEN CULTURE FOR TEACHING MATERIALS - Ela Suhaelah; Ana Nurhasanah; Zerri Rahman Hakim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to find out the stages in developing a handout based on Banten culture for teaching materials and the validity of the handout. This research utilized the Research and Development (R&D) method by Sugiyono, which consisted of 6 steps, namely: (1) problem analysis, (2) data collection, (3) product design, (4) design validation, (5) design revisions, and (6) product trial test. The development of the handout was carried out through the validation test by material experts, media experts, and education experts. Then, to accomplish the limited trial test, a product trial test was conducted after the validation test involving 15 fourth-grade students at SDN Unyur as the research subjects. Findings of this research were that the percentage from the material experts was 95% with a very feasible category. Then, the result from the media expert obtained a percentage of 78% with a feasible category. After that, the result from the education expert indicated that the percentage for the handout was 93% with a very feasible category. Meanwhile, the results of the product trials obtained a percentage of 90% with a very feasible category. Based on these results, it could be concluded that the handout based on Banten culture for the fourth-grade students at SDN Unyur was feasible to be used as teaching materials after going through the six stages of development procedures.